ADHD and ASD traits are differentially associated with orientation sensitivity in a non-clinical adult sample - Varbanov, Vesko; Overton, Paul G.; Stafford, Tom (Frontiers in Psychology, 2025)
ObjectivesResearch indicates that ADHD and ASD are associated with sensory processing difficulties. However, psychophysical testing of this has primarily focused on ASD with no equivalent research on ADHD. The relationship between ADHD, ASD and sensory processing may also be influenced by anxiety. This study investigates whether orientation discrimination performance is differentially related to ADHD and ASD traits in a non-clinical adult sample, and whether anxiety statistically explains these associations.MethodsWe measure visual orientation discrimination thresholds using a method of constant stimuli in a two-alternative forced choice paradigm with an adaptive, randomly interleaved procedure and a one up three down design. The task results are compared to reported trait expressions of ADHD, ASD and anxiety via correlational analysis. Following on this we conduct a mediation analysis to assess the possible mediating role of anxiety.ResultsThe ADHD and ASD trait expressions were associated with similar sensory processing abnormalities. The panic and generalized anxiety traits were only specifically associated with the ADHD-Hyperactive type and respective sensory thresholds. Such effects were not observed for any ASD traits.ConclusionsThese findings suggest that while both ADHD and ASD traits are linked to reduced orientation sensitivity, only ADHD traits—particularly hyperactivity—show specific associations mediated by anxiety. This points to distinct underlying mechanisms in the sensory processing profiles of ADHD and ASD, with anxiety playing a more prominent role in ADHD-related impairments.